ZW, XY, and yet ZW: Sex chromosome evolution in snakes even more complicated - Augstenová, Barbora; Johnson Pokorná, Martina; Altmanová, Marie; Frynta, Daniel; Rovatsos, Michail; Kratochvíl, Lukáš (Evolution; international journal of organic evolution, 2018)
Snakes are historically important in the formulation of several central concepts on the evolution of sex chromosomes. For over 50 years, it was believed that all snakes shared the same ZZ/ZW sex chromosomes, which are homomorphic and poorly differentiated in "basal" snakes such as pythons and boas, while heteromorphic and well differentiated in "advanced" (caenophidian) snakes. Recent molecular studies revealed that differentiated sex chromosomes are indeed shared among all families of caenophidian snakes, but that boas and pythons evolved likely independently male heterogamety (XX/XY sex chromosomes). The historical report of heteromorphic ZZ/ZW sex chromosomes in a boid snake was previously regarded as ambiguous. In the current study, we document heteromorphic ZZ/ZW sex chromosomes in a boid snake. A comparative approach suggests that these heteromorphic sex chromosomes evolved very recently and that they are poorly differentiated at the sequence level. Interestingly, two snake lineages with confirmed male heterogamety possess homomorphic sex chromosomes, but heteromorphic sex chromosomes are present in both snake lineages with female heterogamety. We point out that this phenomenon is more common across squamates. The presence of female heterogamety in non-caenophidian snakes indicates that the evolution of sex chromosomes in this lineage is much more complex than previously thought, making snakes an even better model system for the evolution of sex chromosomes.
Keywords: sex determination; heteromorphic sex chromosomes; reptiles; Squamata; Heterochiasmy